PKM TONGUE TWISTER TRAINING FOR MTS MAMBAUL ULUM PAITON PROBOLINGGO STUDENTS - Tirmidi Tirmidi; Farihatul Qomariah; Lailatut Tarwiyah; Nabila Annisa; Riska Binti Fatatin Azizah (Universitas Pahlawan Tuanku Tambusai, 2025)
The ability to speak English is an essential skill in the era of globalization. However, students at MTs Mambaul Ulum Paiton still experience difficulties in pronouncing English words. This happens, one of the reasons, because the lack of practice in pronouncing English words in everyday life. This training program aims to improve the ability to pronounce English words correctly through tongue twister training method. The implementation of the method includes theory-based and practice-based training sessions. The training is carried out in 5 ( five ) meetings which is weighted 105 minutes in each meeting. Pre-test and post-test were carried out to evaluate the effectiveness of the training.